EVALUATION OF THE ROLE OF D-DIMER, FERRITIN PARAMETERS IN THE PROGNOSIS OF COVID-19 PATIENTS - Pham Dinh , Duy; Le Quang , Tri; Tang Thi Mong , Thu; Nguyen Trong , Nghia; Nguyen Tho , Quang (Tạp chí Y Dược Thực hành 175, 2024)
Background: COVID-19 has spread worldwide from December 2019 to the present. Many biological markers have been used to predict poor outcomes, contributing to early detection and improving patient management. Objective: To evaluate the role of D-dimer and Ferritin parameters in predicting the severity of COVID-19 patients. Methods: Cross-sectional descriptive design combined with a prospective study on 293 patients with positive RT-PCR results for SARS-CoV-2 at Military Hospital 7A; Demographic characteristics, vaccination history, underlying disease, and laboratory parameters including D-dimer and ferritin were collected. Patients were divided into two groups based on disease severity: mild group (n=208), and severe group (n=85). Results: The median age of the study population was 49 (34-62), with 50.9% were male patients. The severe COVID-19 group had significantly higher ferritin and d-dimer levels compared to the mild COVID-19 group. ROC curve analysis, serum Ferritin concentration ≥ 602.5 Microg/L predicted severe COVID-19 with a sensitivity of 68.2% and specificity of 90.9%. Conclusion: Early Ferritin analysis in COVID-19 patients could effectively predict the severity of the disease.